Coupled Evolution of Plate Tectonics and Basal Mantle Structure. (6th January 2021) - Cao, Xianzhi; Flament, Nicolas; Müller, R. Dietmar
Abstract: The relationships between plate motions and basal mantle structure remain poorly understood, with some models implying that the basal mantle structure has remained stable over time, while others suggest that it could be shaped by the aggregation and dispersal of supercontinents. Here we investigate the evolution of mantle flow driven by end‐member plate tectonic models over 1 Gyr. We implement a tectonic scenario in which supercontinent reassembly occurs by introversion, and consider three distinct references frames that result in different net lithospheric rotation. Our flow models predict a dominant degree‐2 mantle structure most of the time. We analyze the relationship between imposed tectonic velocities and deep mantle flow, and find that at spherical harmonic degree 2, the maxima of lower mantle radial flow and temperature follow the motion path of the maxima of surface divergence. It may take ∼160–240 Myr for lower mantle structure to reflect plate motion changes when the lower mantle is reorganized by slabs sinking onto basal thermochemical structures, and/or when slabs stagnate in the transition zone before sinking to the lower mantle. Basal thermochemical structures move at less than 0.6°/Myr in our models, with a temporal average of 0.16°/Myr when there is no net lithospheric rotation, and between 0.20 and 0.23°/Myr when net lithospheric rotation exists and is induced in the lower mantle. Our results suggest that basal thermochemical structures are not stationary, but rather linked to global plate motions and plate boundary reconfigurations, reflecting the dynamic nature of the coevolving plate‐mantle system. Plain Language Summary: Plate tectonic theory, underpinned by a multitude of observations, requires that the tectonic plates and the mantle coevolve. However, whether the lowermost part of the mantle is involved in this evolution, and its relationship with surface plate motions, is poorly known. We build end‐member absolute plate motions models extending back to 1 billion years, and then model mantle convection using time‐dependent surface velocities from plate tectonic models as a boundary condition. We find that the long‐wavelength lower mantle radial flow field and temperature field follow the motion path of the long‐wavelength surface divergence. It may take ∼160–240 Myr for the lower mantle structure to reflect major plate motion changes and plate boundary reconfigurations when the lower mantle is reorganized by sinking slabs sinking onto basal mantle structures, and/or when slabs stagnate in the mantle transition zone (∼410–660 km) before sinking to the lower mantle due to the larger viscosity of lower mantle. Our results suggest that the basal mantle is not stationary, but rather evolves driven by surface plate motions, indicating that the lithosphere and the entire mantle constitute a coevolving dynamic system. Key Points: Our reconstructions of the plate‐mantle system back to 1 Ga show that deep mantle structures are mobile and shaped by plate motions It may take ∼160–240 Myr for deep mantle structure to reflect major changes in plate boundary configurations In the presence of continents, the deep mantle structure is dominantly degree‐2